2014
DOI: 10.1055/s-0034-1389913
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Tissue Distribution of Ketorolac and its Enantiomers in Rats

Abstract: The difference in tissue distribution of Ketorolac and its enantiomers were investigated in wistar rats. Separate high performance liquid chromatographic method was developed and validated for determination of Ketorolac and its enantiomers. Oyster BDS (150 × 4.6 mm id., 5 μm particle size) column was used for determination of concentration of Ketorolac. Ketorolac enantiomers were determined using Chiral-AGP column (100 × 4.0 mm I.D., particle size 5 μ, Chrom tech Ltd, Sweden). Detection was done at wavelength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…A-Gln was approved in clinical use about 50 years ago, but the techniques for enantiomers separation were not well developed, and the selective pharmacokinetic study was almost nonexistent. Pharmacokinetics of enantiomers may be stereoselective [8] , [9] , [10] , [11] , [12] , and chiral inversion may occur [13] , [14] , [15] , [16] in vivo or in vitro; hence the pharmacokinetic and chiral inversion studies of enantiomers become necessary.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…A-Gln was approved in clinical use about 50 years ago, but the techniques for enantiomers separation were not well developed, and the selective pharmacokinetic study was almost nonexistent. Pharmacokinetics of enantiomers may be stereoselective [8] , [9] , [10] , [11] , [12] , and chiral inversion may occur [13] , [14] , [15] , [16] in vivo or in vitro; hence the pharmacokinetic and chiral inversion studies of enantiomers become necessary.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…The intent of this note is to further critically evaluate the published data and provide additional perspectives. Despite the well-planned experimental design that involved time dependent pharmacokinetic sampling from the various tissues, the authors have failed to report the stereoselective pharmacokinetics of ketolorac derived from plasma in this study [1]. Such data would have enabled comparing and contrasting the tissue levels with those observed in the plasma for both ketolorac enantiomers.…”
mentioning
confidence: 98%
“…The investigation of Dubey et al (2013) showed that stereoselectivity of ketolorac was not entirely dependent on the presystemic metabolism although the propensity in the observed stereoselectivity appeared to be different after intravenous as compared to that of the oral administration [2,3]. In view of the earlier reported stereoselective pharmacokinetics of ketolorac and the possibility for chiral inversion in certain tissues, the recent work of Dubey et al (2015) assumes high importance [1]. Hitherto a detailed tissue distribution study of ketolorac enantiomers in the rats examining the pharmacokinetics has not been reported in the literature.…”
mentioning
confidence: 99%
See 2 more Smart Citations